Meningkatkan Hasil Belajar Pendidikan Kewarganegaraan Melalui Metode Diskusi Menggunakan Peta Konsep Pada Siswa Kelas IV SD Negeri 018 Tambusai Utara - Retha Br Tarigan (STKIP Rokania Pasir Pangaraian, 2018)
The purpose of this research is to improve the learning outcomes of Civics by using concept map strategy. The type of research is classroom action research with research procedure consisting of planning, action implementation, observation, and reflection. The results showed that in the first cycle the percentage of students' learning completeness to 78% and to 89% in the evaluation of cycle II as a refinement cycle I. From the results of this study can be concluded that the improvement of learning through concept map strategy for fourth graders Elementary School 018 North Tambusai this managed to improve student learning outcomes so that learning mastery achieved optimally